Sekuritisasi Pandemi Covid-19 Di Indonesia - Prasojo Prasojo; M Lukman Arifianto; Azhar Irfansyah (Jurnal Kajian Ilmiah, 2023)
This study aims to examine the theory of securitization and relate it to the strategy undertaken by the Indonesian government to deal with the Covid-19 pandemic. This is interesting to study because the main demands on every country during this pandemic are; what to do, how to do it, is the strategy for handling Covid-19 by the state the answer for the wider community? This question is the duty of the state to be able to provide a sense of security for the community. The research methodology will be carried out under a qualitative umbrella with the thick description method. The results found in this study were that Indonesia initially considered Covid-19 only as a health problem before the WHO gave an appeal. It can be said that this appeal is a norm that was formed in which Indonesia must implement an appeal from WHO. This is a turning point for the Indonesian government in dealing with the spread of Covid-19. In addition to forming this justification, the Indonesian people are also an important object in tackling the spread of COVID-19 in Indonesia where the level of discipline of the Indonesian people determines the success of the Indonesian Government's direction in the issue of the spread of COVID-19 as a security issue.